The Cost Efficiency of Commercial Banks in Namibia - Kandaswamy R, Vijayakumar; Ndowora, Vimbai Enia; Gnitchogna, Rodrigue (IJRDO - Journal of Business Management, 2018)
The current study aims to measure the cost efficiency of the 4 commercial banks, namely Bank Windhoek, First National Bank, Nedbank and Standard Bank Namibia over 13 years. Two vastly used models aid the research with each model falling in one of the main classes of measuring a bank’s efficiency. Firstly, a parametric approach namely the Stochastic Frontier Approach (SFA) gives the cost efficiency scores of an individual bank within the 13 years of study. Secondly, a ratio based model, the CAMEL model which makes use of 18 ratios under Capital Adequacy, Asset Quality, Management, Earnings quality and Liquidity will give a general ranking of the cost efficiency of the banks. The general efficiency of all the banks decreases significantly from 2003 to 2016.